IMPACT OF COVID-19 PANDEMIC ON PEDIATRIC OCULAR TRAUMA DURING SUMMER BREAK - ZAFAR, R; MALIK, SN; UZAIR, N (Biological and Clinical Sciences Research Journal, 2024)
The COVID-19 pandemic reshaped nearly every aspect of daily life, imposing restrictions that altered children’s routines and environmental exposures. Objective: To study the impact of the COVID-19 pandemic on pediatric ocular trauma during summer break in a tertiary care eye hospital in Pakistan. Methods: This retrospective comparative study was conducted at the Department of Pediatric Ophthalmology and Strabismus at Al-Shifa Trust Eye Hospital, Rawalpindi during summer vacation, spanning from 1st June to 31st August of 2019 (a year before covid-19 pandemic, i.e pre-pandemic period) and same duration in 2020 (pandemic period). Data was collected from 385 pediatric patients who were admitted for ocular trauma treatment during these two study periods. Results: Among 385 patients, 190 cases arise from pre-pandemic and 195 from pandemic period. In both study periods, the majority involved male patients (60%), with female cases making up 40%. The average age of affected children remained consistent at 8.5 years, and the most frequently affected age group was 6-10 years. Blunt trauma cases increased from 45% (86 cases) pre-pandemic to 50% (98 cases) during the pandemic, likely due to increased time spent indoors with potential household hazards. Penetrating injuries, however, decreased from 30% (57 cases) to 25% (49 cases), possibly reflecting reduced outdoor play. Conclusion: It is concluded that the COVID-19 pandemic led to an increase in household-related pediatric ocular trauma, with a higher proportion of severe injuries and delayed treatment impacting recovery outcomes